Performance of a combined system of electrolysis and granular activated carbons for leachate treatment of Jeram sanitary landfill, Malaysia - Mohammed Riyadh Khaleel (2015)
In this study, raw leachate collected from Jeram Sanitary Landfill (JSL) was characterized. The landfill leachate is a complex substance that contains toxic compounds, organic matter, ammonium, heavy metals and colloidal solids and a variety of pathogens potentially contaminate surface water and groundwater. The effluents are complicated to deal with and biological processes are totally inefficient for the toxic nature of stabilized leachate. Hence, there are coagulation-flocculation and adsorption process used to treat leachate. The coagulation-flocculation does by electrolysis process and adsorption by activated carbon. The raw leachate was treated using electrolysis treatment technique in which iron and stainless steel electrodes were utilized. In the electrolysis process, different voltages of 3, 6, 12, 18 and 24 volt and different retention times (RT) of 5, 10, 15, 20, 30, 40 and 50 min were used. The filtration process by quartz filter is subsequent treatment after electrolysis process. The adsorption process by using granular activated carbon (GAC) obtained from coconut shell (GACC) and oil palm shell (GACP) was final treatment after electrolysis and filtration processes. In the adsorption process, different AC dosages of 2, 4, 6, 8 and 10g/l and different contact times (CT) of 1, 2, 3, 4, 5, 6, 8, 10 and 13 hr were used. In electrolysis, the biochemical oxygen demand (BOD₅) removal efficiency was 68% and the chemical oxygen demand (COD) removal efficiency of 56% was achieved using the iron electrode. Total dissolved solids (TDS) removal efficiency of 55% was obtained at 20 min RT. Optimum total suspended solids (TSS) removal efficiencies of 69 and 75% were obtained using iron and stainless steel electrodes, respectively. Salinity removal efficiency was 53% and turbidity removal efficiency was 96%. The pH value was 9.4 at 40 min RT using iron electrode. The lowest electrical conductivity (EC) value was recorded as 156μs/cm using iron electrode. In adsorption process, the BOD₅ removal efficiency was 95%, while the COD removal efficiency was 88%. Total nitrogen (TN) removal efficiency was recorded as 98.7%, while phosphate (PO₄) removal efficiencies of 84 and 82% were obtained at CT of 4 (GACC) and 2 hr, (GACP) respectively. TDS removal efficiency was obtained as of 66 and 75% at 4 hr CT of GACC and GACP, respectively. Optimum TSS removal efficiency was 90%. Salinity removal efficiencies using GACC and GACP were 81 and 74%, respectively. Turbidity removal efficiency of 95% was the highest removal efficiency recorded at 6 hr. The pH was 8.93 for both GACC and GACP. Using GACC and GACP, EC values were recorded as 102 and 83μs/cm, respectively. After several combinations of voltage were used for the electrolysis process, where, 40 min RT and 24 volt were selected as the best combination for the highest removal efficiency. Also, GAC dosage of 10 g/l at 6 hr CT yielded the highest removal efficiency. Generally, iron electrode is the cheaper and more resistant to corrosion than stainless steel. The results obtained from the iron electrode were close to stainless steel results. On the other hand, GACP is the cheaper than GACC. Also, GACP is abundantly produced in Malaysia as a biomass waste generated from agricultural activities. In conclusion, GACP can be considered a promising environmental-friendly adsorbent for the treatment of landfill leachate.